2019
DOI: 10.1002/rcs.2030
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative validation of bone cut accuracy of a pinless smart touch‐screen navigation system device in total knee arthroplasty

Abstract: Purpose Primary objective in most of the published literature on computer‐assisted total knee arthroplasty (TKA) has so far been the comparison of axial alignment and components position, obtained either through navigation systems or through conventional instrumentation. We have found no studies aimed at assessing the intraoperative reliability of a navigation system in relation to bone cuts height. Aim of our study was therefore to establish bone cut accuracy of a pinless navigation system. Methods From Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It laid the foundation for further nursing research. Subsequently, scholars from various countries have also carried out extended nursing research one after another, and their definitions are not the same [15]. So far, the concept of continuous care has not been uniformly defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It laid the foundation for further nursing research. Subsequently, scholars from various countries have also carried out extended nursing research one after another, and their definitions are not the same [15]. So far, the concept of continuous care has not been uniformly defined.…”
Section: Discussionmentioning
confidence: 99%
“…It is pointed out that the changes of proprioceptive sensation and neuromuscular control are the main reasons of these effects [14]. Keitkamp et al have indicated that balance training can significantly increase the standing time of one leg on the unstable interface, but strength training cannot enhance it [15]. Meanwhile, balance training can increase the maximum contractile strength of knee flexion and extension under isokinetic condition.…”
Section: Introductionmentioning
confidence: 99%
“…Surgeons performing total knee arthroplasty (TKA) and considering different alignment options and instrumentation are interested in the accuracy and time it takes to make the distal and posterior femoral bone resections that determine the setting of the femoral component [ 7 ]. Technology proponents argue that robotic, navigation, and patient-specific instrumentation more accurately hit the femoral target than manual instruments [ 12 , 14 , 22 , 28 ]. Whereas manual instrument proponents argue that technology lengthens the operation, adds expense, and induces stacked errors arising from transforming images into a 3D model, planning the resection planes, and registering instruments [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve that, a computer-assisted, pinless navigation device (Knee 2.6, Brainlab AG, Feldkirchen, Germany) was used for 30 patients. The accuracy of this system has already been investigated in several studies and was verified to be a precise and reliable pinless navigation system [ 7 , 8 , 9 , 10 ]. The setup consisted of a stand-alone computer with infrared cameras, controlled by a touch screen, and a pointer with reflector spheres as well as a reflector array.…”
Section: Methodsmentioning
confidence: 99%